Identification of peripheral CD154+ T cells and HLA-DRB1 as biomarkers of acute cellular rejection in adult liver transplant recipients. (29th October 2020) - Boix, F; Legaz, I; Minhas, A; Alfaro, R; Jiménez–Coll, V; Mrowiec, A; Martínez–Banaclocha, H; Galián, J A; Botella, C; Moya–Quiles, M R; Sanchez–Bueno, F; Robles, R; et al.
Summary: Decreasing graft rejection and increasing graft and patient survival are great challenges facing liver transplantation (LT). Different T cell subsets participate in the acute cellular rejection (ACR) of the allograft. Cell-mediated immunity markers of the recipient could help to understand the mechanisms underlying acute rejection. This study aimed to analyse different surface antigens on T cells in a cohort of adult liver patients undergoing LT to determine the influence on ACR using multi-parametric flow cytometry functional assay. Thirty patients were monitored at baseline and during 1 year post-transplant. Two groups were established, with (ACR) and without (NACR) acute cellular rejection. Leukocyte, total lymphocyte, percentages of CD4 + CD154 + and CD8 + CD154 + T cells, human leukocyte antigen (HLA) mismatch between recipient–donor and their relation with ACR as well as the acute rejection frequencies were analysed. T cells were stimulated with concanavalin A (Con-A) and surface antigens were analysed by fluorescence activated cell sorter (FACS) analysis. A high percentage of CD4 + CD154 + T cells ( P = 0·001) and a low percentage of CD8 + CD154 + T cells ( P = 0·002) at baseline were statistically significant in ACR. A receiver operating characteristic analysis determined the cut-off values capable to stratify patients at high risk of ACR with high sensitivity and specificity for CD4 + CD154 + ( P = 0·001) and CD8 + CD154 + T cells ( P = 0·002). In logistic regression analysis, CD4 + CD154 +, CD8 + CD154 + and HLA mismatch were confirmed as independent risk factors to ACR. Post-transplant percentages of both T cell subsets were significantly higher in ACR, despite variations compared to pretransplant. These findings support the selection of candidates for LT based on the pretransplant percentages of CD4 + CD154 + and CD8 + CD154 + T cells in parallel with other transplant factors. Graphical Abstract: